Effects of World Health Organization Labour Care Guide Utilization for Safe Motherhood during Intrapartum Period through Midwives - Dost Muhammad, Rukhsana; Masih, Sarfraz; Afzal, Muhammad (Journal of Neonatal Surgery, 2025)
Background: The World Health Organization's (WHO) Labour Care Guide (LCG) is a critical document designed to advance maternal and newborn outcomes in the course of Labour. It is vital to uphold high-quality intrapartum care that responds to international global health standards. Objective: Effects of the WHO LCG by midwives to promote safe motherhood during the intrapartum period. Methodology: This multi-centered quasi-experimental study includes data from 216 delivery cases, collected through 43 midwives who fulfilled the inclusion criteria, i.e., minimum 2 years of job experience and running an independent maternity clinic, using the WHO LCG. 43 midwives from 15 centers in Quetta, Pakistan, were selected to assess their competency level after training about the WHO LCG. Descriptive statistics were applied for the competency level of midwives, a chi-square test was used to compare the safe motherhood outcome pre- and post-implementation of WHO LCG. p<0.05 was considered significant. Results: The mean competency level score of midwives was 93.1 ± 3.6 percent, which is excellent. The maternal health care outcomes pre and post implementation of LCG guideline improved significantly except obstructed Labour (p=0.068) and uterine rupture (p= 0.082), which improved insignificantly, with pre-training occurrence of 12 (5.6%) and 3 (1.4%) cases, respectively. Neonatal outcomes also show significant improvement except stillbirth cases (p=0.082), which improve insignificantly with pre-implementation of LCG, occurring cases of 3 (1.4%). Conclusion: WHO LCG has a significant effect on maternal and neonatal health care. Moreover, the competency level of midwives was also improved after training